2015
DOI: 10.1007/s12663-015-0856-4
|View full text |Cite
|
Sign up to set email alerts
|

Superolateral Dislocation of Intact Mandibular Condyle: A Case Report and Review of Literature

Abstract: Anteromedial fracture dislocation of the mandibular condyle is common but a superolateral dislocation of an intact condyle is quite rare. This type of dislocation is often misdiagnosed or completely overlooked and hence inadequately addressed. We report a case of a 41-year-old male patient who experienced superolateral dislocation of the intact condyle with symphysis fracture and panfacial fracture following a road-traffic accident, and review of literature of superolateral dislocations from 1967 to 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The rest 6 cases were type I dislocated. The Worthington described his type of case with the term unusual and the information was not available for the case of Radhakrishkna (Table III) (Table IV) [1][2][3][4]7,10,12,13,[22][23][24][25][26][27][28] while 34 dislocations (46.26%) was managed by surgical modalities [5][6][7]9,11,14,[16][17][18][19][20][21][22]24,26,27,29] while no treatment was given for 2 cases (2.98%) resulting in fibrosseous ankylosis [4] (Table V). It can be concluded that most of all surgeons had used open reduction techniques for management of supero-lateral dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…The rest 6 cases were type I dislocated. The Worthington described his type of case with the term unusual and the information was not available for the case of Radhakrishkna (Table III) (Table IV) [1][2][3][4]7,10,12,13,[22][23][24][25][26][27][28] while 34 dislocations (46.26%) was managed by surgical modalities [5][6][7]9,11,14,[16][17][18][19][20][21][22]24,26,27,29] while no treatment was given for 2 cases (2.98%) resulting in fibrosseous ankylosis [4] (Table V). It can be concluded that most of all surgeons had used open reduction techniques for management of supero-lateral dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 16 publications reviewed, 12 (75%) were Indian (Tab. II) [1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. 30 patients were involved with a mean age of 31.87 years.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The average treatment time was 11.78 days (Tab. II) [1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Literature Reviewmentioning
confidence: 99%